About micro- and nanoscale gold in the veil of gold-bearing territories (on the example of a mineralization site in the basin of the river Adamikha, Amur region) - I. V. Kuznetsova; A. I. Dementienko (Georesursy, 2024)
The article identifies the problem of the need to take into account micro- (1 mm to 0.12 microns) and nanoscale (<0.12 microns) gold in placers and weathering crusts in order to increase the objectivity of their and eroded ore objects potential assesment. The results of technological studies of gold-bearing deluvial deposits in the valley of the Adamikha river basin (Amur region) are presented. A quantitative assessment of the content of micro- and nanogold by fractions of loose material was made. It was found that in the studied sample of such material (weighing 50 kg), the major part (78%) refers to native gold with a dimension of < 0.12 microns. Including 0.1% is in concentrator minerals, and 3.5% of the fraction (<3 microns), probably colloidal, is in technical solutions of wet sieve. Moreover, 3/4 of the total amount (18% visible and 57% invisible) of gold is concentrated in the fraction (1–0.5 mm). It is established that, taking into account the free invisible gold, the resources of the precious metal of the object under study increase by 3.4 times. The possibility of a more objective quantitative assessment of the Au potential of promising areas, taking into account the content of fine gold, is shown. Possible ways of solving the problem of a more reliable assessment of geological reserves and estimation of forecast gold resources, taking into account the knowledge of the quantities of micro- and nanoscale fractions, are proposed. The authors believe that studies of the forms of allocation and distribution, including invisible (<0.12 microns) gold in placers and weathering crusts will contribute to a more correct assessment of the studied gold-bearing objects and territories with the possibility of increasing the real resource potential of the precious metal in the region.